2017
DOI: 10.1111/jfb.13253
|View full text |Cite
|
Sign up to set email alerts
|

El Niño episodes coincide with California moray Gymnothorax mordax settlement around Santa Catalina Island, California

Abstract: The hypothesis that El Niño events influence the settlement patterns of the California moray Gymnothorax mordax is tested. The pelagic larval duration (PLD) of larval G. mordax is unknown, but studies on leptocephalus of related species suggest that larvae are long-lived, up to 2 years. Gymnothorax mordax, an elusive predatory species and the only muraenid off the coast of California, is considered abundant in the waters around Catalina Island. Thirty-three individuals were collected from Two Harbors, Catalina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…While it is evident that larval dispersal and spatial coagulation of larval cohorts [80] vary because of dynamic nearshore and offshore oceanographic conditions [81–85], our AD modeling also illustrates the importance of considering large-scale, climatic variation in assessments of population connectivity. ENSO and other large-scale climate-driven phenomena can exhibit small temporal-scale variability that enhance or suppress larval dispersal [8589]. Consistent with evidence of ENSO influencing population connectivity of ocean-dwelling species across the Hawaiian archipelago and elsewhere in the Pacific [19, 90], we found that ENSO likely influences S. stimpsoni larval dispersal (Figure 1).…”
Section: Discussionsupporting
confidence: 82%
“…While it is evident that larval dispersal and spatial coagulation of larval cohorts [80] vary because of dynamic nearshore and offshore oceanographic conditions [81–85], our AD modeling also illustrates the importance of considering large-scale, climatic variation in assessments of population connectivity. ENSO and other large-scale climate-driven phenomena can exhibit small temporal-scale variability that enhance or suppress larval dispersal [8589]. Consistent with evidence of ENSO influencing population connectivity of ocean-dwelling species across the Hawaiian archipelago and elsewhere in the Pacific [19, 90], we found that ENSO likely influences S. stimpsoni larval dispersal (Figure 1).…”
Section: Discussionsupporting
confidence: 82%
“…However, with even the shortest Pacific to Atlantic connectivity timescales being greater than 2 years, our results suggest that the tipping point for any species requiring a single‐summer transit to avoid Arctic winters is highly improbable. The >2‐year connectivity timescales found here are beyond the PLD of rock lobsters at 18 months (Bradford et al, ) or even California morays at ~2 years (Higgins et al, ) but does not necessarily preclude a stepping‐stone style transit with species reproducing along the journey (Selkoe & Toonen, ). Planktonic species, such as the diatom N. seminae which inspired this study (Reid et al, ), are not limited by PLD, and so >2‐year transits cannot automatically be ruled out on that basis.…”
Section: Discussionmentioning
confidence: 70%
“…Kernel density plots are displayed on the right with mean size (vertical lines) of kelp bass consumption by L H range (mm) and age class, in parentheses. L H were converted to age class date following the regression line presented in Higgins et al ( 2017 ) …”
Section: Resultsmentioning
confidence: 99%
“…This may in part help explain why we observed significantly smaller kelp bass sizes consumed in 2015 relative to all other years, where they had the largest L value. During the entirety of 2015, Santa Catalina Island was enveloped by the strongest El Niño since 1983 (Higgins et al 2017 ). This resulted in a complete loss of kelp canopy cover (B.H., C.L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation